Variation in human bone bioerosion during the Late Eneolithic/Bronze Age in Moravia (Czech Republic): A novel approach to BSE‐SEM image quality and quantity assessment. (12th August 2022) - Pankowská, Anna; Žižková, Andrea; Kapusta, Jaroslav; Moník, Martin
Abstract: Human bones from Late Eneolithic graves and Bronze Age settlement pits in Moravia (Czech Republic) were studied to reconstruct their post‐mortem histories based on the distribution of their microbial destruction. Backscattered electrons in a scanning electron microscope (BSE‐SEM) were used for visual assessment of bioerosion. Visual data from the histological analysis were transformed into quantitative data using the Waikato Environment for Knowledge Analysis (WEKA) toolkit. The results show that the presence of bioerosion is different between the two groups of samples. The bones from settlement pits display extensive bioerosion whereas the bones from graves display no or arrested bioerosion. The absence of bioerosion in graves is most probably linked with tomb burials of Corded Ware Culture. Given the tombs are frequently not preserved archaeologically, the state of bone bioerosion may serve as an indicator of their existence.